Area‐based study identifies risk factors associated with missed antenatal corticosteroid prophylaxis in women delivering preterm infants. (23rd September 2016) - Gagliardi, Luigi; Amador, Carolina; Puglia, Monia; Mecacci, Federico; Pratesi, Simone; Sigali, Emilio; Tomasini, Barbara; Rusconi, Franca; ,
Abstract: Aim: All women delivering a preterm infant should receive antenatal corticosteroid prophylaxis, but many miss this opportunity. We determined the risk factors associated with missed prophylaxis in a geographically defined area of Italy. Methods: We prospectively studied all mothers who delivered babies between 24 and 31 completed weeks of gestation, from 2009 to 2013, in all maternity units in Tuscany. Results: Of 1232 mothers, 186 (15.1%) did not receive prophylaxis. The risk was higher in migrant mothers, with an adjusted risk ratio (RR) of 1.28 and 95% confidence interval (95% CI) of 1.04–1.56, and in mothers hospitalised for less than 24 hours (RR 4.09, 95% CI: 2.90–5.78). Preterm prelabour rupture of membranes (RR 0.63, 95% CI: 0.41–0.96) and maternal antepartum transfer (RR 0.24, 95% CI: 0.18–0.32) were protective. Hospital level at birth and gestational age did not influence the prophylaxis rate. The population‐attributable fractions were 50.4% for late hospital admissions and 10.2% for migrant status. Conclusion: In a highly organised network of hospitals, neither level of care nor gestational age influenced prophylaxis. Timely arrival of women in hospital, better recognition of the imminence of delivery and tighter steroids administration guidelines are the most relevant targets to further increase prophylaxis. Abstract :